Advances in Electrospun Nanofiber Membranes for Dermatological Applications: A Review - Yuanyuan Han; Hewei Wei; Qiteng Ding; Chuanbo Ding; Shuai Zhang (Molecules, 2024)
In recent years, a wide variety of high-performance and versatile nanofiber membranes have been successfully created using different electrospinning methods. As vehicles for medication, they have been receiving more attention because of their exceptional antibacterial characteristics and ability to heal wounds, resulting in improved drug delivery and release. This quality makes them an appealing choice for treating various skin conditions like wounds, fungal infections, skin discoloration disorders, dermatitis, and skin cancer. This article offers comprehensive information on the electrospinning procedure, the categorization of nanofiber membranes, and their use in dermatology. Additionally, it delves into successful case studies, showcasing the utilization of nanofiber membranes in the field of skin diseases to promote their substantial advancement.